2000
DOI: 10.1681/asn.v11122344
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of On-Line Hemodiafiltration and High-Flux Hemodialysis

Abstract: Abstract. Some of the morbidity associated with chronic hemodialysis is thought to result from retention of large molecular weight solutes that are poorly removed by diffusion in conventional hemodialysis. Hemodiafiltration combines convective and diffusive solute removal in a single therapy. The hypothesis that hemodiafiltration provides better solute removal than high-flux hemodialysis was tested in a prospective, randomized clinical trial. Patients were randomized to either on-line postdilution hemodiafiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(34 citation statements)
references
References 39 publications
1
26
3
Order By: Relevance
“…In both the Turkish OL-HDF and FRENCHIE studies, no difference in the overall hospitalization rate was observed between the two groups (Supplement 9 forest plot 1.2), but in the ESHOL Study, the hospitalization rate was lower in the high-flow online HDF group (RR, 0.78; 95% CI, 0.67-0.90; p = 0.001). In terms of quality of life, our meta-analysis of six prospective clinical trials (excluding observational studies) [68][69][70][71][72][73] found no significant difference between the online HDF and HD groups.…”
Section: Key Question 32mentioning
confidence: 71%
“…In both the Turkish OL-HDF and FRENCHIE studies, no difference in the overall hospitalization rate was observed between the two groups (Supplement 9 forest plot 1.2), but in the ESHOL Study, the hospitalization rate was lower in the high-flow online HDF group (RR, 0.78; 95% CI, 0.67-0.90; p = 0.001). In terms of quality of life, our meta-analysis of six prospective clinical trials (excluding observational studies) [68][69][70][71][72][73] found no significant difference between the online HDF and HD groups.…”
Section: Key Question 32mentioning
confidence: 71%
“…In both the Turkish OL-HDF and FRENCHIE studies, no differences in overall hospitalization rates were observed between the two groups, but in the ESHOL study, the hospitalization rate was lower in the high-flow online HDF group (RR, 0.78; 95% CI, 0.67 to 0.90; p < 0.01). In terms of quality of life, a meta-analysis performed on six prospective clinical trials, excluding observational studies [ 58 63 ], found no significant difference between the online HDF and HD groups.…”
Section: Chapter 3 Dialysis Membrane and Modality For Hemodialysismentioning
confidence: 99%
“…Hemofiltration and hemodiafiltration can be applied for toxins that can be applied hemodialysis. Unlike hemodialysis, it is also effective in toxins with higher 8,12,13 . Due to the increasing technical need and transportation difficulties, its use in poisoning cases is limited 8,14 .…”
Section: Contınuous Hemofiltration and Hemodiafiltrationmentioning
confidence: 99%